TECHNIQUE OF DESIGN HYDRO-SAND-STREAM PERFORATION THROUGH SEVERAL COLUMNS - Качмар, Юрій Дмитрович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The problem of calculating of length channel which produced by jet fluid with sand in formation through several cemented columns is decided. Columns, cement rings and formation rock considered as consistently placed partitions of given thickness with their initial velocity of material destruction. Middle axial velocity of jet in each partition defined with due regard for distance from the nozzle and thickness. An example of calculating the parameters of carrying perforation of well are described.